Dietary Deoxynivalenol Contamination and Oral Lipopolysaccharide Challenge Alters the Cecal Microbiota of Broiler Chickens - Lucke, Annegret; Böhm, Josef; Zebeli, Qendrim; Metzler-Zebeli, Barbara U. (Frontiers in Microbiology, 2018)
Dietary deoxynivalenol (DON) impairs the intestinal functions and performance in broiler chickens, whereas little is known about the effect of DON on the gastrointestinal microbiota. This study evaluated the impact of graded levels of dietary DON contamination on the cecal bacterial microbiota, their predicted metabolic abilities and short-chain fatty acid (SCFA) profiles in chickens. In using a single oral lipopolysaccharide (LPS) challenge we further assessed whether an additional intestinal stressor would potentiate DON-related effects on the cecal microbiota. Eighty one-day-old chicks were fed diets with increasing DON concentrations (0, 2.5, 5, and 10 mg DON per kg diet) for 5 weeks and were sampled after half of the chickens received an oral LPS challenge (1 mg LPS/kg bodyweight) 1 day before sampling. The bacterial composition was investigated by Illumina MiSeq sequencing of the V3-5 region of the 16S rRNA gene. DON-feeding decreased (p < 0.05) the cecal species richness (Chao1) and evenness (Shannon) compared to the non-contaminated diet. The phyla Firmicutes and Proteobacteria tended to linearly increase and decrease with increasing DON-concentrations, respectively. Within the Firmicutes, DON decreased the relative abundance of Oscillospira, Clostridiaceae genus, Clostridium and Ruminococcaceae genus 2 (p < 0.05), whereas it increased Clostridiales genus 2 (p < 0.05). Moreover, increasing DON levels linearly decreased a high-abundance Enterobacteriaceae genus and an Escherichia/Shigella-OTU (p < 0.05). Changes in the bacterial composition and their imputed metagenomic capabilities may be explained by DON-related changes in host physiology and cecal nutrient availability. The oral LPS challenge only decreased the abundance of an unassigned Clostridiales genus 2 (p = 0.03). Increasing dietary concentrations of DON quadratically increased the cecal total SCFA and butyrate concentration (p < 0.05), whereas a DONLPS interaction indicated that LPS mainly increased cecal total SCFA, butyrate and acetate concentrations in chickens fed the diets that were not contaminated with DON. The present findings showed that even the lowest level of dietary DON contamination had modulatory effects on chicken’s cecal bacterial microbiota composition and diversity, whereas the additional oral challenge with LPS did not potentiate DON effects on the cecal bacterial composition.